Exploring how women negotiate pregnancy in respect to food behaviours and weight status : an interpretative phenomenological study - Tweheyo, Ritah (2016)
This study is a longitudinal exploration of women’s eating behaviours and weight status during motherhood starting from pre-conception, through pregnancy and into the early postpartum period. The study aimed to explore how women negotiate pregnancy in the context of food and weight status using IPA. The rationale was to capture from the diverse voices of different women what is important to them at these different time points and collectively how this informs behaviour in the motherhood journey. The participants consisted of three different, randomly selected sample sets of women 20- 40 years. Focus groups were carried out with 10 never pregnant women, followed by serial individual interviews with five currently pregnant women, and five women who had recently given birth, interviewed at 2 different time points. The findings highlight a change in women’s priorities described in superordinate themes along the motherhood cycle. Women’s priorities changed starting in pre-conception with a strong sense of self and realisation of limited time for childbearing, to focussing on the baby at the expense of the self, during and after pregnancy. The findings strongly show that women’s eating has emotional, biological and gendered meanings during the transition to motherhood. Socialisation, social events, expectations and peer support also strongly influenced how women negotiated conflict in this continuum. There are tensions in the postpartum period between the new focus on the baby (emerging during pregnancy), which prescribes healthful eating, and the stresses of a new motherhood lifestyle which reverts women to emotional eating (present preconceptually). In negotiating these tensions, women adopt the digital discourse as part of self-support behaviours in addition to trust and desire for the support of HCPs and significant others. The findings have implications for lifestyle interventions that acknowledge these tensions, women’s priorities and their coping strategies.
HydraID: hull:14556 Hydra Discover Access Group: public ETD Collection: ETDInstituteForHealthStudies
Keywords: Health and social care